Who is responsible for doping in sports? The attribution of responsibility in the German print media - Starke, C.; Flemming, F. (Communication & Sport, 2017)
The fight against doping has been one of the most profound challenges in the world of (media-) sports. However, communication research has not addressed the mediated attribution of responsibility for this problem. Drawing on the distinction between episodic and thematic framing, this study analyzes the attribution of responsibility in three quality German national newspapers. We find that responsibility for causing performance enhancing drugs (PEDs) use is equally attributed to the individual and systemic levels, while responsibility for finding solutions is directed at the systemic level. Individual responsibility attributions occur more frequently in articles with an episodic news frame. Given the often proclaimed ambiguous role of the media with regard to PED use, the study attaches particular importance to the self-attribution of responsibility by the media. Our findings show that the media neglect to discuss their own role and do not see themselves as responsible for the problem of doping. This study demonstrates that the investigation of mediated responsibility attribution provides a fruitful new approach to the research on media and PED use in sports.